Language maintance and the preservation of ethanic identity: a case of Malay Muslims in Southern Thailand - Kama, Nonglaksana; Yamirudeng, Munirah (2010)
Language is known to have an effect on ethnic identity in that language retention of a mother tongue acts as a stronger connector to the ethnic community for such persons as compared to those who do not retain the language. For cultural groups who hold knowledge of ethnic language as a core value, language shift can lead to a lose of ethnic identity, cultural fragmentation and “non-authentic” expressions of ethnicity This paper attempts to explore the symbolic role that language plays in the evolution and maintenance of ethnic identity within the Malay Muslim community in southern Thailand. It discusses how the Malay language was used as a symbol to create and sustain the Malay identity on the ways in which Malay Muslims today understand ethnic identity, and how ethnic language fits into their own ethnic self-identifications Therefore, this paper attempt to answer the question of Why Malay language constitutes vital elements in the maintenance of Malay ethnic identity among the Malays of southern Thailand? As a result two facts have been identified regarding the language and ethnicity link among Malay Muslims. First, Malay language is seen as a relevant ethno-cultural marker and its usage is limited within family, relatives and close friends. Second, Malay language is preserved in combination with Thai making many Malay Muslims bilingual, which is quite typical in the southern border provinces of Thailand.